Design of a potent reactivator of tabun-inhibited acetylcholinesterase--synthesis and evaluation of (E)-1-(4-carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide (K203) - Musilek, Kamil; Jun, Daniel; Cabal, Jiri; Kassa, Jiri; Gunn-Moore, Frank; Kuca, Kamil (Journal of medicinal chemistry, 2007)
Acetylcholinesterase reactivators are crucial antidotes for the treatment of organophosphate intoxication. Among the organophosphates, with the exception of soman, tabun (GA) intoxications are the least responsive to treatment with commercially available therapeutics. A rational design was used to increase reactivation ability and decrease the toxicity of the novel reactivator. (E)-1-(4-carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide (K203) has better properties than previously tested compounds in vitro and, therefore, is a potential candidate for the treatment of GA intoxication in vivo.
Keywords: Cholinesterase Inhibitors; Chemical Warfare Agents; chemické bojové látky; Structure-Activity Relationship; racionální návrh léčiv; Oximes; acetylcholinesterasa; Cholinesterase Reactivators; Pyridinium Compounds; vztahy mezi strukturou a aktivitou; organofosfáty; kinetika; pyridinové sloučeniny; reaktivátory cholinesterasy; Drug Design; oximy; Acetylcholinesterase; cholinesterasové inhibitory; Kinetics; Organophosphates